Aksi Coastal Clean Up di Pantai Tanah Abang Desa Malaku Kecamatan Seram Utara Kabupaten Maluku Tengah - Dwi Partini (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Cleanliness is very important in human life, in the context of daily habitual behavior and in terms of the environment. An environment that is clean from garbage reflects the healthy behavior of the community, besides that it is also soothing to the eyes. An environment that is not kept clean will certainly interfere and can even cause a disease and also disrupt the balance of biota in an ecosystem. This activity aims to carry out a clean-up action on the Tanah Abang beach in Malaku Village, North Seram District. The coastal clean up action was carried out together with mosque youth with the method of sorting the types of waste. The result is that 65% of inorganic waste comes from residents who visit the beach in the form of plastic bottles, glass bottles, raffia rope, plastic food packaging and coconut shells used to drink young coconuts. While 35% is organic waste from nature in the form of dry leaves and tree branches. The collected garbage is burned so that the beach becomes cleaner and more worthy to visit as a place of refreshing.